Marketing Mix Strategy To Increase Room Occupancy At Sanctoo Suites & Villas - Ni Luh Pratiwi Eca Putri; Made Sudiarta; I Gusti Agung Bagus Mataram (Jurnal Sains Terapan Pariwisata, 2021)
This research focuses on the analysis of the marketing mix strategy used by the Sales & Marketing department at Sanctoo Suites & Villas and also this study aims to determine the most relevant marketing mix strategies used to increase the room occupancy at Sanctoo Suites & Villas. The data collection methods used in this study were participant observation, structured interviews, questionnaires, and documentation. The analysis technique used in this study consists of qualitative descriptive analysis, IFAS (Internal Factor Analysis Summary) Matrix, EFAS Matrix (External Factor Analysis Summary), Internal-External Matrix (IE), and analysis with a SWOT matrix (Strength, Weaknesses, Opportunities, Threats). The result of the IFAS matrix (Internal Factor Analysis Summary) analysis score is 2.99 and the EFAS matrix (External Factor Analysis Summary) score is 2.86 therefore in the IE (Internal-External) Matrix the position of the current marketing mix strategy is at cell 5, Internal-External Matrix (IE), which is called growth and stability strategies through horizontal integration. The analysis with the SWOT matrix (strength, weaknesses, opportunities, threats) result 10 alternative strategies that can be applied to increase the occupancy rate of Sanctoo Suites & Villas rooms.